The Influence of School Education on the Professional Identity of Healthcare Professionals: The Formalization of Knowledge Transfer in Schools and Clinical Environments - Abrantes, António (2019)
The purpose of this chapter is to discuss the influence of school education on the formation of professional identity of radiology professionals. The research approach selected was based on a bibliographic review regarding the concepts involving professional identity and the transfer of knowledge at the school level, and the methods utilized to translate it into the clinical environment. These two themes were approached in two different researches, one aiming to evaluate whether or not the skills that students perceive as being acquired at the degree level will correspond to professional field demands, and the other aiming to collect perceptions regarding the clinical support provided to students by tutors. There is continuity between school socialization and professional socialization processes, allowing the implementation at the school level of the real needs of the radiology professional, and the contents provided to students prior to the clinical environment were sufficient to assure the development of professional competencies.